A new geometrical approach for rapid LED processing by using femtosecond laser. (November 2015) - Reklaitis, I.; Grinys, T.; Tomašiūnas, R.; Puodžiūnas, T.; Mažulė, L.; Sirutkaitis, V.; Lin, C.H.; Yang, C.C.
Abstract: A new original method to reduce time and resource consuming photolithography mask production operations has been suggested. By means of femtosecond laser direct writing, thus, gaining cleaner surrounding than for nano- and pico-second pulse processing, a 45° angle ablation geometry has been proven. LED chip separation trenches and n -GaN layer exposure were made simultaneously saving from one fundamental processing and alignment step without adverse effect from the laser-processing on the quantum well region. Abstract : Highlights: 45° ablation led to a simple, rapid and accurate fs laser LED׳s processing method. A LED technology with reduced processing and critical alignment steps. LED chip separation trenches and n-GaN layer exposure were made simultaneously.